2009
DOI: 10.1371/journal.pone.0004316
|View full text |Cite
|
Sign up to set email alerts
|

PECAM-Independent Thioglycollate Peritonitis Is Associated With a Locus on Murine Chromosome 2

Abstract: BackgroundPrevious studies have demonstrated that knockout or inhibition of Platelet/Endothelial Cell Adhesion Molecule (PECAM, CD31) in a number of murine strains results in impaired inflammatory responses, but that no such phenotype is seen in the C57BL/6 (B6) murine background.Methodology/Principal FindingsWe have undertaken a quantitative trait locus (QTL) mapping effort between FVB/n (FVB) and B6 mice deficient for PECAM to identify the gene or genes responsible for this unique feature of B6 mice. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…However, these differences were found not to be significant (P Ͼ 0.13). Although this difference was not statistically significant, this finding is in line with previously published reports that have described the C57BL/6 strain as a hyperinflammatory mouse model (26), which partially explains its popularity in the field of immunology.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, these differences were found not to be significant (P Ͼ 0.13). Although this difference was not statistically significant, this finding is in line with previously published reports that have described the C57BL/6 strain as a hyperinflammatory mouse model (26), which partially explains its popularity in the field of immunology.…”
Section: Discussionsupporting
confidence: 90%
“…Our in vivo studies reported here were limited to PMN interactions in acute inflammatory settings. Based on previous studies (22,26), we predict that monocytes would behave similarly.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This observed inhibition of leukocyte recruitment compares well with the reported inhibition of recruitment by other inhibitors of the NF-κB- [33] and 5-LO- signaling pathways [34] and with the suggestion that mPGES-1 might be a likely candidate for a role as PCAM-1 independent modulator of leukocyte recruitment [35]. More detailed future analysis of the bioactive depsides in diverse animal models of inflammation e.g.…”
Section: Discussionsupporting
confidence: 85%